Using real estate estimation to determine investment efficiency - Nesterenko, I. (Ways to Improve Construction Efficiency, 2015)
Using real estate appraisal to determine the effectiveness of investment.The basic indicators for evaluating the effectiveness of the project in real estate appraisal.